Insilico and invitro investigations of alpha-glucosidase inhibitory activity of phenolic constituents of tetracera indica - Muhammad Alhassan, Alhassan; Ahmed, Qamar Uddin; Sarian, Murni Nazira; Khatib, Alfi (University Putra Malaysia, 2017)
The leaves of Tetracera indica are used in traditional medicine for the treatment of diabetes mellitus. This study was aimed at investigating the phytochemical constituents present in T. indica leaves and their activity against digestive enzyme (alphaglucosidase) which may be part of the mechanism of the antidiabetic effect of the plant. Crude methanolic extract from the leaves of T. indica which demonstrate significant alpha glucosidase inhibitory activity was separated and purified by column chromatography of Silica gel, ODS and Sephadex LH-20, the structures of the isolated compounds were identified by UV, 1H-NMR, 13C-NMR and MS spectroscopic techniques. Five flavonoids were isolated from the leaves of T. indica, and these compounds were identified as follows: 5,7-dihydroxy-8-methoxyflavone (wogonin), 5,7,8-trihydroxyflavone (norwogonin), quercetin, 5- hydroxy-7-methoxyflavone (tectochrysin) and 41, 3, 5, 7-tetrahydroxyflavone (kaempferol). The isolated compounds show moderate to strong activity against alphaglucosidase enzymes. Insilco studies using molecular docking show the mode of interactions of the compounds with the active site residues and their binding energies. The results of this study reveal that alphaglucosidase inhibition is one of the primary mode of action of T.indica antidiabetic effect.